PRODUKSI BIODIESEL DARI MINYAK BIJI JARAK (Jatropha curcas) DENGAN MENGGUNAKAN KATALIS KALIUM HIDROKSIDA (KOH) Production of Biodiesel from Jatropha Seed (Jatropha Curcas) Oil Using KOH as Catalyst - Kasturi, Kasturi; Riza, Medyan; Supardan, Muhamad Dani (Jurnal Hasil Penelitian Industri, 2013)
Nowadays, the use of fuel as the primer source of energy has been carriedout using petroleum classified as non-renewable fossil. The product needed hassignificantly increased along with its uses in industry and transportation lastly spurringthe necessity of a new alternative source of energy. This research was aimed to obtain bestoperating condition to product biodiesel via transesterification process of jatropha seedusing 3% wt. of KOH as catalyst. Condition process of producing biodiesel were at 30, 40,50, 60 and 70ï°C of process temperatures, 200, 300 and 400 rpm of agitation speeds, and1:12, 1:14, and 1:16 of mole ratios between jatropha seed and methanol. The result of thisresearch showed that the higher ratio between Jatropha curcas and methanol the higherbiodiesel obtained. While for the operating condition, the faster agitation speed alsoinfluenced in the more amount of biodiesel yield. Best operating temperature obtained wasat 60ï°C. The analysis of the product including density, viscosity, acid number and flashpoint were 846 kg/m3, 5 cSt, 0,67 mg KOH/gr and 35ï°C, respectively.